2017
DOI: 10.1016/j.jpainsymman.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Trial of Ascertaining Individual Preferences for Loved Ones' Role in End-of-Life Decisions (TAILORED) Study: A Randomized Controlled Trial to Improve Surrogate Decision Making

Abstract: Context Patients with terminal illnesses often require surrogate decision makers. Prior research has demonstrated high surrogate stress, and that despite standards promoting substituted judgment, most patients do not want their surrogates to make pure substituted judgments for them. It is not known how best to help loved ones fulfill the surrogate role. Objectives To test the effectiveness of an intervention to help surrogate decision makers. Methods 166 patients (41% with ALS and 59% with gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 40 publications
(50 reference statements)
1
44
0
2
Order By: Relevance
“…Participants were recruited at hospital-based outpatient clinics, 27,29,31,33 a surgery clinic 26 dialysis clinics, 30,28 and medical centers. 33,32 Regarding the timing of the interventions, 3 studies focused on interventions for patients near death by limiting participants to patients having a high comorbidity score 30 or a diagnosis of stage III or IV cancer. 31,32 In 6 studies, the intervention was delivered in the same clinical settings where participants were recruited, 26 -29,30,32 whereas in 2 studies, it was delivered via home visits 33 or videoconferences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were recruited at hospital-based outpatient clinics, 27,29,31,33 a surgery clinic 26 dialysis clinics, 30,28 and medical centers. 33,32 Regarding the timing of the interventions, 3 studies focused on interventions for patients near death by limiting participants to patients having a high comorbidity score 30 or a diagnosis of stage III or IV cancer. 31,32 In 6 studies, the intervention was delivered in the same clinical settings where participants were recruited, 26 -29,30,32 whereas in 2 studies, it was delivered via home visits 33 or videoconferences.…”
Section: Resultsmentioning
confidence: 99%
“…The interventions were conducted using trained facilitators. Excluding 2 studies 27,29 that did not specify the health-care profession of trained facilitators, most interventions (62.5%) were conducted by trained nurses, 28,26,30,32,33 and 1 (12.5%) was delivered by trained social workers. 31 The frequency and duration of intervention sessions varied, ranging from 1 to 6 sessions (mean = 2.5 sessions) delivered weekly or biweekly and lasting from 20 to 90 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This negotiation should begin at the earliest time possible, as it will help to develop the bond between the patient and the medical team [14]. Studies have shown that making decisions regarding a patient’s management is very stressful for the healthcare proxy [15]. During these stressful times, the decision-making process is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…15 A third found that conversations between terminally ill hospitalized patients and their surrogates which are actively facilitated by the health care team improve subsequent decision making. 16 Little has been written about how to conduct advance care planning conversations during routine office visits. 17,18 Based on these informative works, our own observations, and dialog with colleagues, we propose a family medicine-focused approach to advance care planning.…”
mentioning
confidence: 99%